Managing Dynamic Networks Organizational Perspectives of Technology Enabled Inter-firm Collaboration - Klein, Stefan; Poulymenakou, Angeliki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Collaboration of organizations reshapes traditional managerial practices and creates new inter-organizational contexts for strategy, coordination and control, information and knowledge management. Heralded as organizational forms of the future, networks are at the same time fragile and precarious organizational arrangements, which regularly fail. In order to investigate the new realities created by technology-enabled forms of network organizations and to address the emerging managerial challenges, this book introduces an integrative view on inter-firm network management. Centred on a network life cycle perspective, strategic, economic and relational facets of business networking are explored. The network management framework is illustrated onto a broad range of European inter-firm network examples in various industries rendering insights for new management practices.
Framing Inter-firm Network Management -- Networks as Orchestrations: Management in IT-enabled Inter-firm Collaborations -- Network Management Framework -- Elaboration on Network Management $1 (BCore Themes in Select Industry Settings -- Connecting Company Strategy and Network Identity -- Institutional Design of Mixed-mode Electronic Marketplaces -- Portfolio Management of R&D Collaborations in Mobile Commerce -- The Role of Social Capital in Managing Relationships with IT Suppliers -- The Influence of Power Relations on Interorganisational Identification in Buyer-Supplier Relationships of the Automotive Industry -- Performance Measurement in Supply Chain Networks -- Examining the Emerging Dynamics of an Information Infrastructure -- Unraveling the Virtual University -- Conclusions -- Organizing Principles for Inter-firm Networks.s
Keywords: Business; Organization; Planning; Information technology; Business -- Data processing; Business and Management; IT in Business; Organization; Electronic books